Pembrolizumab in combination with ipilimumab as second-line or later therapy for advanced non–small-cell lung cancer: KEYNOTE-021 cohorts D and H. (April 2019) - Gubens, Matthew A.; Sequist, Lecia V.; Stevenson, James P.; Powell, Steven F.; Villaruz, Liza C.; Gadgeel, Shirish M.; Langer, Corey J.; Patnaik, Amita; Borghaei, Hossein; Jalal, Shadia I.; Fiore, Joseph; Saraf, Sanatan; et al.
Highlights: KEYNOTE-021 evaluated pembrolizumab plus ipilimumab in second-line advanced NSCLC. Antitumor activity was observed with pembrolizumab 2 mg/kg plus ipilimumab 1 mg/kg. Efficacy in these heavily pretreated patients was similar to historical controls. This combination dosed every 3 weeks was associated with meaningful toxicity. Abstract: Objectives: Combination immunotherapy may result in improved antitumor activity compared with single-agent treatment. We report results from dose-finding and dose-expansion cohorts of the phase 1/2 KEYNOTE-021 study that evaluated combination therapy with anti‒programmed death 1 (PD-1) antibody pembrolizumab plus anti‒cytotoxic T-lymphocyte antigen-4 (CTLA-4) antibody ipilimumab in patients with previously treated advanced non–small-cell lung cancer (NSCLC). Materials and methods: Eligibility criteria stipulated histologically/cytologically confirmed advanced NSCLC and treatment failure on ≥1 prior systemic therapy (platinum-based chemotherapy or targeted therapy for patients with EGFR / ALK aberrations). In the dose-finding cohort, patients initially received pembrolizumab 10 mg/kg plus ipilimumab 1 or 3 mg/kg once every 3 weeks for 4 cycles followed by pembrolizumab 10 mg/kg monotherapy for up to 2 years. Based on emerging published data, subsequent patients received pembrolizumab 2 mg/kg plus ipilimumab 1 mg/kg. Objective response rate (ORR; primary efficacy endpoint) was assessed per RECIST version 1.1 by blinded, independent central review. Phase 2 hypothesis that ORR would be greater than the 20% rate for historical controls was evaluated using the exact binomial test. Results: Fifty-one patients were enrolled; 71% received ≥2 prior lines of therapy. No dose-limiting toxicities occurred at any dose level. Among patients who received pembrolizumab 2 mg/kg plus ipilimumab 1 mg/kg (n = 44), ORR was 30% (95% CI, 17%–45%), but not statistically significantly >20% ( P = 0.0858). Median progression-free survival in this group was 4.1 (95% CI, 1.4–5.8) months; median overall survival was 10.9 (95% CI, 6.1–23.7) months. With pembrolizumab 2 mg/kg plus ipilimumab 1 mg/kg, incidences of treatment-related adverse events, grade 3–5 treatment-related adverse events, and immune-mediated adverse events and infusion reactions were 64%, 29%, and 42%, respectively. Conclusions: In patients with heavily pretreated advanced NSCLC, pembrolizumab plus ipilimumab showed evidence of antitumor activity, but was associated with meaningful toxicity.